BASAL CELL SKIN CARCINOMA: CLINICAL FEATURES, DIAGNOSIS AND MODERN TREATMENT METHODS - Косимова М.; Одилжонова М. (Innovate Conferences, 2025)
Basal cell carcinoma (basalioma) is the most common malignant skin tumor, accounting for 70–80% of all non-melanoma malignancies. Its incidence continues to rise, particularly among the elderly and those with fair skin. Despite its low metastatic potential, basalioma is characterized by locally destructive growth and a tendency to recur. The aim of this study was to analyze the clinical and epidemiological characteristics, diagnostic methods, and effectiveness of various treatment approaches for basal cell carcinoma.